2015
DOI: 10.1016/j.proenv.2015.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Seawater Intrusion Modeling on Groundwater Confined Aquifer in Semarang

Abstract: The focus of this study is to identify and describe of a seawater intrusion in confined aquifer modelling in Semarang with a descriptive quantitative analytical method. The results showed potentially experiencing seawater intrusion which increased of 0.575 km 2 /years. Seawater intrusion models divide to 3 models are the western route have a maximum error is 27.9%, then the middle route have the maximum error is 41.1% and the eastern route have the maximum error is 40%. In 2035, the seawater intrusion on weste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 3 publications
(3 reference statements)
0
8
0
3
Order By: Relevance
“…The simulation model showed that the rate of seawater intrusion is about 0.20 km (with mangrove as a system component), and is about 0.30 -0.40 km (without mangrove as a system component). The trend of seawater intrusion in Jakarta is not different from seawater intrusion in Semarang which has increased by 0.575 km 2 years -1 (Suhartono, Purwanto & Suripin, 2015). Table 3 also shows that mangrove has an important role to play to reduce the rate of intrusion in Jakarta.…”
Section: Prediction Of Seawater Intrusion In Jakartamentioning
confidence: 84%
“…The simulation model showed that the rate of seawater intrusion is about 0.20 km (with mangrove as a system component), and is about 0.30 -0.40 km (without mangrove as a system component). The trend of seawater intrusion in Jakarta is not different from seawater intrusion in Semarang which has increased by 0.575 km 2 years -1 (Suhartono, Purwanto & Suripin, 2015). Table 3 also shows that mangrove has an important role to play to reduce the rate of intrusion in Jakarta.…”
Section: Prediction Of Seawater Intrusion In Jakartamentioning
confidence: 84%
“…This increasing salinization is monitored from several shallow dug wells and deep wells scattered around the city. Recently, a salinization phenomenon is estimated to reach 4 km inland from the coastline (Suhartono et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Perubahan unsur yang dominan dari intrusi air laut dapat dilihat dari komposisi kimia air tanah diantaranya dari ion klorida (Cl) (Singhal dan Gupta, 2010; Purnama 2010; Cahyadi et al, 2017). Unsur kimia dari air ta-nah yang dominan terdampak intrusi ditunjukkan dari kandungan nilai sodium (Na) dan klorida (Cl) yang relatif tinggi (Suhartono et al, 2015, Cahyadi et al, 2017Hounsinou, 2020).…”
Section: Pendahuluanunclassified